2017
DOI: 10.1016/j.fuproc.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants for biodiesel: Additives prepared from extracted fractions of bio-oil

Abstract: Unlike petroleum diesel, the chemical structure of biodiesel makes it prone to oxidation during long-term storage, thus involving fuel quality deterioration. Therefore, the addition of antioxidants is usually required to meet the quality standards for biodiesel commercialization. Synthetic sterically-hindered phenols have been usually employed for this purpose as free radical scavenging antioxidants. However, naturally occurring phenolics are also available, for example, in the bio-oil produced in the pyrolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 36 publications
0
31
0
3
Order By: Relevance
“…The mixture was heated up to 60 °C for 3 h at atmospheric pressure and continuously stirred in a batch reactor under reflux. More details about the preparation method can be found elsewhere [23]. Several batches of biodiesel were prepared to get the amount needed for this work, around 25 L. After preparation, all the biodiesel batches were mixed and kept at −18 °C until its utilization.…”
Section: Biodiesel Productionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mixture was heated up to 60 °C for 3 h at atmospheric pressure and continuously stirred in a batch reactor under reflux. More details about the preparation method can be found elsewhere [23]. Several batches of biodiesel were prepared to get the amount needed for this work, around 25 L. After preparation, all the biodiesel batches were mixed and kept at −18 °C until its utilization.…”
Section: Biodiesel Productionmentioning
confidence: 99%
“…The final additive was mainly composed of biodiesel, with a concentration higher than 80%. More details about the preparation method can be found in the work by García et al [23].…”
Section: Preparation Of the Antioxidant Additivementioning
confidence: 99%
See 2 more Smart Citations
“…The effect of auto-oxidation was greater than that of photo-oxidation. The use of antioxidants [76], or the combination of biodiesel and diesel fuel, is an important way to improve the oxidation stability of biodiesel. Focke et al [77] have found that phenolic (DTBHQ) and phosphite (Naugard P) antioxidants can improve the antioxidant properties of COB fuel.…”
Section: Oxidation Stabilitymentioning
confidence: 99%